DINAMIKA ARUS DI LAUT FLORES DAN SEKITARNYA TAHUN 2004-2006 - Nur Hasanah, Yulia
The aim of this study is to analyze the current dynamics in the Flores Sea and the surrounding area based on data from the Hybrid Coordinate Ocean Model (HYCOM) in 2004 untill 2006 with a resolution of 1/8o, using statistical approaches and signal analysis. The results of this study show that spatially, the current dynamics in this region are affected by current circulation from the Java Sea, Makassar Strait, Banda Sea and water mass circulation from northern part of Flores Sea at the east side. The distribution of the currents in respect to depth can be divided into several layers based on seasonal effects and current movement at certain depths in accordance with the characteristics of the Indonesian Throughflow (ITF). At the surface layer of 0-100 meters, the seasonal effects (northwest monsoon and southeast monsoon) affect the current dynamics in the Flores Sea. There is southern current from Makassar Strait moving to the southern part of Flores Sea along whole year. Meanwhile a depth of 150-300 meters, ITF currents from the Makassar Strait flow toward the southern part of the Flores Sea which can then reach to the waters of Nusa Tenggara and moving out trough Ombai Strait. The maximum velocity of this current is 0,36 m/s which occurs during the southeast monsoon at a depth of 150 meters. In the eastern part of the Flores Sea, the an ITF branch indicated come from Halmahera Sea at a depth of 400-800 meters with a maximum velocity of 0,33 m/s during the northwest monsoon